Formulation and Evaluation of Microspheres Containing Aceclofenac - Y.Phalguna; G.Supriya; A.Tejasvi; D.Narasimha; G.Gopala Krishna (International Journal of Pharmacy and Analytical Research, 2014)
Aceclofenac, a non-steroidal anti-inflammatory drug (NSAID) The chemical name of aceclofenac is Glycolic acid, [o(2,6 dichloroanilino) phenyl] acetate. Adverse effect of aceclofenac is headache, nausea, vomiting, bone marrow problems, dizziness constipation. Elimination half-life is 4 hrs. The main objective of this research work was to prepare hydroxyl propyl methyl cellulose and eudragit microspheres loaded with aceclofenac and invtro relese study.In the present study, solvent evaporation method is used for preparation microspheres. The polymers hydroxylpropyl methylcellulose and eudragit was dissolved and added to the 0.2% PVA solution and stirred it for 2 hrs. Microspheres were spherical shape and smooth surface. Infrared spectra showed identical peaks of drug and polymers. Drug entrapment efficiency was found to be (72.32%). In vitro release studies were performed by using shaking flask method about (89.59 %) drug was released in 12 hrs.